Examining the relationship between U.S. incarceration rates and population health at the county level - Robert R. Weidner; Jennifer Schultz (Elsevier, 2019)
A collateral consequence of mass incarceration in the United States is its negative effects on population health. Using data from 2015, this study examines the relationship between incarceration rates and population health for a national sample of U.S. counties. To obtain unbiased estimates of the effect of incarceration on health, we use multivariate models which account for the endogeneity of incarceration rates when determining their effect on population health by employing an instrumental variable approach where the robust instrumental (exogenous) variable per capita corrections expenditures is used to predict incarceration rate. We then estimate population health outcomes as a function of predicted incarceration rate alongside factors such as public health spending, indicators of health behavior and control variables in models explaining county-level population health. Consistent with findings from prior research on individuals, families and at the state level, results of our analyses indicate that higher levels of incarceration are associated with higher levels of both morbidity (percentage reporting fair or poor health) and mortality (life expectancy). Implications of these findings for health and criminal justice policy, as well as research, are considered. Keywords: United States, Incarceration rate, Population health, Health status, Life expectancy, County health expenditures